HUBUNGAN ANTARA EFEKTIFITAS KOMUNIKASI ANTARPRIBADI DENGAN PRESTASI AKADEMIK(Studi Korelasi Efektifitas Komunikasi Antarpribadi antara Guru dan Murid dengan Prestasi Akademik Murid Program Akselerasi SMA Negeri 3 Surakarta Tahun Ajaran 2014/2015) - Pratiwi, Metalia Putri, Palupi, M.A, Joko Sutarso, M.Si (2015)
Interpersonal communication applied in the learning process between teachers and students in the acceleration program of SMAN 3 Surakarta. Academic year of acceleration program takes less than eight months, which the academic achievement must be obtained each student to keep up a class. The purpose of this research is to know significant correlation of interpersonal communication between teacher and student with academic achievement on student acceleration program of SMA Negeri 3 Surakarta. Interpersonal communication effectiveness is measured by the five dimensions; openness, empathy, support, and positive sense of equality. This research take sample 59 peoples from 2nd grade students acceleration program of SMA Negeri 3 Surakarta. This is a quantitative explanatif research using Spearman correlation analysis. Results of the research using Spearman correlation showed rs obtained by 0.883 at 0.01 significance level. In the Spearman correlation the Ha is accepted if rs> 0. In conclusion the effectiveness of interpersonal communication has a significant correlation with academic achievement at respectively level of 0.01. Keywords: Interpersonal Communication, Academic Achievement, Quantitative, Correlation